Perception of public towards BRIM in Kampung Raba Sebuyau / Benedict Russell Robert Asai & Jane Anin - Robert Asai, Benedict Russell; Anin, Jane (2012)
For the background of the study, this will answer the question, does the welfare program such as BR1M, help the recipients especially the lower income group and the poor, discuss about research question and research objectives. For the scope of study, this have 3 sections that are, who are the respondents, where is the research conducted and the duration of conducting this research, emphasizing the significant of study where to find what are the important of study this research. For definition of term and concept, there are several terms needed to identify what are welfare, welfare assistance and poverty.